Graphenyldiene: A new sp2-graphene-like nanosheet - Laranjeira, José A.S. [UNESP]; Martins, Nicolas F. [UNESP]; Denis, Pablo A.; Sambrano, Julio R. [UNESP] (Elsevier, 2024)
The race and the discovery of novel two-dimensional (2D) carbon-based materials have been intensified because many are suitable for energy storage systems, thermoelectric devices, and catalysis applications. Therefore, this study introduces to the scientific community a novel 2D nanosheet named graphenyldiene (GPD), which is formed by arranging cyclobutadiene and bi-phenyl groups to create a monolayer with octadecagonal, hexagonal and tetragonal rings. The cohesive energy of GPD is only 1.37 and 0.65 eV/atom higher than graphene and biphenylene, respectively. Molecular dynamics simulations confirmed its structural and thermal stability. The GPD monolayer remains stable, with no significant deformations at around 1000 K, and the disintegration of the geometry occurs only at a temperature of 1500 K, which is characterized by the formation of an amorphous graphdiyne. The GPD electronic structure shows a direct band gap transition, 1.26 eV, at the Γ point. GPD is a promising alternative to electronic devices due to its carrier mobility of around 103.cm2/V.s. Also, the GPD satisfies the Born-Huang criterion for mechanical stability with elastic constants C11 = 157.62 N/m, C12 = 53.66 N/m and C66 = 51.98 N/m. The Bader's topological analysis indicated that all bonds have strong shared shell characteristics. Finally, the vibrational analysis identified 54 modes, where 21 are Raman active, with A1g and E2g modes dominating the spectrum at 1347, 1685 and 1697 cm−1.
Keywords: Biphenyldiene; Biphenylene; Carbon allotrope; Graphene; Graphenyldiene